Histological features and prognostic significance of treatment effect in lymph node metastasis in head and neck squamous cell carcinoma. Issue 2 (4th November 2018) - Scherpelz, Kathryn P; Wong, Anthony C; Lingen, Mark W; Taxy, Jerome B; Cipriani, Nicole A
Abstract : Aims and objectives: Cervical lymph node metastasis in head and neck squamous cell carcinoma (HNSCC) is common. Pre‐operative chemoradiotherapy (preCRT) and postoperative chemoradiotherapy (postCRT) is frequently employed in such patients. The prognostic value of viable SCC, treatment effect or no SCC in resected lymph nodes in patients who received or did not receive preCRT and postCRT was investigated. Methods and results: Resected cervical lymph nodes from 146 patients with HNSCC were evaluated for viable SCC, treatment effect or no SCC. Immunostains for Ki67, cyclin D1, caspase 3 and H2AFX were performed on viable SCC or nucleate keratin debris. Clinical and histological data were correlated with tumour recurrence or persistence. Patients with nucleate keratin debris in lymph nodes had outcomes similar to those with diffuse treatment effect and no SCC. Viable tumour in lymph nodes was associated with worse prognosis in patients who received preCRT ( P  = 0.01). This relative worsening of prognosis was not observed in patients with oropharyngeal SCC or recurrent disease. Lower proliferation index in lymph node SCC was associated with preCRT and with worse outcomes ( P  = 0.0002). Overall, patients who received preCRT or postCRT had outcomes not significantly different from those who did not. Conclusion: The presence of viable SCC in cervical lymph nodes has prognostic import when taken in context with the patient's history. Viable SCC in lymph nodes was significantly associated with worse outcome among patients with non‐oropharyngeal SCC who received preCRT. Nucleate keratin debris should not be considered viable SCC in lymph nodes.